The Analysis Study of Surgical Management, Outcome, Recovery and Complication of Haemorrhoid : A Comprehensive Systematic Review - M.Fahriza Winaldha Nasution; Fadhilla Qudsi Ramadhani; Alya Amanda M Nasution; Muhammad Ghifari Armadi (International Medical Journal Corp. Ltd, 2024)
Background: Despite its prevalence, hemorrhoidal disease remains a major challenge for healthcare systems, often requiring significant resources to manage and treat effectively. This systematic review examines the surgical management of hemorrhoids, focusing on patient outcomes, recovery, and complications based on literature from the past decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Hemorrhoid management offers various surgical options, including SPH, THD, and hemorrhoidal embolization, each providing quicker recovery and reduced pain. Traditional excisional surgery remains the gold standard for long-term outcomes, with pain management strategies enhancing recovery and patient satisfaction.